2023
DOI: 10.1002/anie.202303379
|View full text |Cite
|
Sign up to set email alerts
|

Complexes Featuring a cis‐[MUM] Core (M=Rh, Ir): A New Route to Uranium‐Metal Multiple Bonds

Abstract: Although examples of multiple bonds between actinide elements and main‐group elements are quite common, studies of the multiple bonds between actinide elements and transition metals are extremely rare owing to difficulties associated with their synthesis. Here we report the first example of molecular uranium complexes featuring a cis‐[M →0false→ ${{\rm{ \mathbin{{\stackrel{\textstyle\rightarrow} { {\smash{\rightarrow}\vphantom{_{\vbox to.5ex{\vss}}}} } }} }}}$ U ←0false← ${{\rm{ \mathbin{{\stackre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…50 The U–Rh bond length in 6 is longer than the U–Rh single-bond lengths reported in [U IV I 2 (μ-OAr P -1κ 1 O ,2κ 1 P ) 2 Rh I (μ-I)] 2 (Ar P O − = 2-(diphenylphosphino)-6- tert -butyl-4-methylphenoxide) (2.7601(5) Å), U IV I(μ-I)(μ-OAr P -1κ 1 O ,2κ 1 P ) 3 Rh I (2.7630(5) Å) 95 and U[N(CH 3 )(CH 2 CH 2 NP i Pr 2 ) 2 ](μ-Me) 2 Rh 2 (μ-Me) 4 Mg(C 4 H 8 O) (2.6612(5) Å). 34 The U–Ir bond length (2.8656(3) Å) is shorter than the sum of the covalent single-bond radii of U and Ir (2.92 Å), but longer than the U–Ir single-bond length in complex U[N(CH 3 )(CH 2 CH 2 NP i Pr 2 ) 2 ] [(μ-Me) 2 Ir 2 (μ-Me) 4 Mg(C 4 H 8 O)] (2.6968(4) Å). 34 Nevertheless, the U–Rh/Ir bond lengths observed in 6 and 7 are consistent with the presence of a U–M bonding interaction in these clusters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…50 The U–Rh bond length in 6 is longer than the U–Rh single-bond lengths reported in [U IV I 2 (μ-OAr P -1κ 1 O ,2κ 1 P ) 2 Rh I (μ-I)] 2 (Ar P O − = 2-(diphenylphosphino)-6- tert -butyl-4-methylphenoxide) (2.7601(5) Å), U IV I(μ-I)(μ-OAr P -1κ 1 O ,2κ 1 P ) 3 Rh I (2.7630(5) Å) 95 and U[N(CH 3 )(CH 2 CH 2 NP i Pr 2 ) 2 ](μ-Me) 2 Rh 2 (μ-Me) 4 Mg(C 4 H 8 O) (2.6612(5) Å). 34 The U–Ir bond length (2.8656(3) Å) is shorter than the sum of the covalent single-bond radii of U and Ir (2.92 Å), but longer than the U–Ir single-bond length in complex U[N(CH 3 )(CH 2 CH 2 NP i Pr 2 ) 2 ] [(μ-Me) 2 Ir 2 (μ-Me) 4 Mg(C 4 H 8 O)] (2.6968(4) Å). 34 Nevertheless, the U–Rh/Ir bond lengths observed in 6 and 7 are consistent with the presence of a U–M bonding interaction in these clusters.…”
Section: Resultsmentioning
confidence: 99%
“…34 The U–Ir bond length (2.8656(3) Å) is shorter than the sum of the covalent single-bond radii of U and Ir (2.92 Å), but longer than the U–Ir single-bond length in complex U[N(CH 3 )(CH 2 CH 2 NP i Pr 2 ) 2 ] [(μ-Me) 2 Ir 2 (μ-Me) 4 Mg(C 4 H 8 O)] (2.6968(4) Å). 34 Nevertheless, the U–Rh/Ir bond lengths observed in 6 and 7 are consistent with the presence of a U–M bonding interaction in these clusters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this considerable progress, the chemistry of RE–M bonds is still in its infancy compared with that of transition metals. , With our ongoing interest in the double-layer N-P ligands and metal–metal bonds, we report here the successful isolation and characterization of a series of complexes, 2 , 3 , 5 , 6 , and 7 , which all feature Ce–M (M = Ni, Pd, and Pt) bonds supported by N–P ligand VI or N–CH 2 –P ligand VII (Figure ). Complexes 2 and 3 contain up to four Ce–Pd/Pt bonds, which is the largest number of RE–M bonds ever observed in a molecule.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we found that the double layer N–P ligands are not only effective platforms for the construction of heterometallic clusters with metal–metal bonds 25–31 but also play an important role in the activation of small molecules and catalysis. 32–34 Based on our continuing interest in the construction of heterometallic clusters with metal–metal bonds supported by double layer N–P ligands, we have attempted to synthesize complexes with metal–metal bonds between Mg and coinage metals.…”
Section: Introductionmentioning
confidence: 99%